2015
DOI: 10.3233/rnn-140420
|View full text |Cite
|
Sign up to set email alerts
|

Selegiline promotes NOTCH-JAGGED signaling in astrocytes of the peri-infarct region and improves the functional integrity of the neurovascular unit in a rat model of focal ischemia

Abstract: Purpose: Our experiments aimed at exploring potential neurorestorative mechanisms of selegiline, a compound routinely used in the treatment of Parkinson's disease and previously shown to improve the functional recovery of stroke patients. Methods: Selegiline was administered continuously via osmotic mini-pumps between 48 and 216 hours following middle cerebral artery occlusion (MCAO) in rats. Twenty-four hours before sacrifice, the animals underwent magnetic resonance imaging (MRI). After decapitation, the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Previous studies indicated expression of JAG and DLL on reactive brain astrocytes, and astrocytes can induce Notch signalling by themselves or with other cell types such as neural stem cells. [31][32][33][34] Moreover, a recent study demonstrated that optic nerve astrocytes express JAG1 with no significant expression of DLL. 35 Since retinal astrocytes are immigrants from the optic nerve, 36 it is possible that they also express Notch ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated expression of JAG and DLL on reactive brain astrocytes, and astrocytes can induce Notch signalling by themselves or with other cell types such as neural stem cells. [31][32][33][34] Moreover, a recent study demonstrated that optic nerve astrocytes express JAG1 with no significant expression of DLL. 35 Since retinal astrocytes are immigrants from the optic nerve, 36 it is possible that they also express Notch ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Cilostazol is a commonly used antiplatelet drug, which prevents the pathological detachment of astrocyte foot processes or PCs and also stimulates VEGFR2 expression and PC proliferation, thereby protecting the NVU integrity and promoting neurovascular protection 104 . Notch‐Jagged signaling in astrocytes is increased in selegiline‐treated MCAO rats compared with control, helping to preserve the capillary network after IS 105 . Treatment with tPA inhibits the secretion of glial cell‐derived trophic factors and damages PCs, but edaravone can reverse the damage, and maintains NVU integrity after tPA treatment 106 .…”
Section: Is Therapies Targeting the Nvumentioning
confidence: 99%
“…The exact mechanism of memantine transport across the BBB requires more detailed investigation; however, therapeutic targeting of memantine to the CNS via OCT-dependent drug delivery may prove to be an effective mechanism to enhance the utility of this neuroprotective drug in treatment of ischemic stroke. Other OCT transport substrates that may be effective as stroke therapeutics include the D2/D3 receptor agonist pramipexole [84,85], the monoamine oxidase inhibitor selegiline [86], and the nicotinic receptor agonist varenicline [87]. Further data is required to determine the functional role of OCT isoforms expressed at the BBB in the setting of ischemic stroke.…”
Section: Endogenous Bbb Transportersmentioning
confidence: 99%